2021
DOI: 10.1088/1742-6596/1963/1/012121
|View full text |Cite
|
Sign up to set email alerts
|

Studying The Topographic and Morphology Structure of CdO:In Thin Films

Abstract: Cadmium oxide thin films was deposited by thermal oxidation method, on glass substrate with the thickness (300 ∓ 10)nm and deposition rate (1.25)nm/sec. The films doped with the (In) with the different ratios(l,2,3)%. The topographic and morphology structures of films are characterized by(XRD), (SEM) and (AFM) techniques. XRD investigation showed all films have polycrystalline structures with the preferred orientation (111) plane. The results of microscopic testing proved that presence the nanostructures and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…From the scanning electron microscopy (SEM) analysis, it is apparent that the shape of CdONPs is nearly spherical in nature (Figure 2(a)). Energy‐dispersive X‐ray spectroscopy (EDAX) analysis is a good analytical technique for the elemental analysis or chemical characterization of an unknown sample [36–39] . Here the amount of elements Cd and O varies periodically along with atom size, and it includes 5.74 % of Cd (maximum) along with 94.26 % of O (maximum).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the scanning electron microscopy (SEM) analysis, it is apparent that the shape of CdONPs is nearly spherical in nature (Figure 2(a)). Energy‐dispersive X‐ray spectroscopy (EDAX) analysis is a good analytical technique for the elemental analysis or chemical characterization of an unknown sample [36–39] . Here the amount of elements Cd and O varies periodically along with atom size, and it includes 5.74 % of Cd (maximum) along with 94.26 % of O (maximum).…”
Section: Resultsmentioning
confidence: 99%
“…Energy-dispersive X-ray spectroscopy (EDAX) analysis is a good analytical technique for the elemental analysis or chemical characterization of an unknown sample. [36][37][38][39] Here the amount of elements Cd and O varies periodically along with atom size, and it includes 5.74 % of Cd (maximum) along with 94.26 % of O (maximum). The EDAX analysis clearly has shown that there are no other elements present in the CdONPs composition (Figure 2(b)).…”
Section: Characterization Of Cdonpsmentioning
confidence: 99%